Novel platinum (II) and platinum (IV) complexes exhibit potent chemotherapeutic properties in breast and skin cancer models - Farah, Roudy (2022)
Following the discovery of cisplatin and its chemotherapeutic potential, many researchers started developing novel variations of platinum-based complexes to test their efficicacy in treating different types of cancer. The present study aims to determine the chemotherapeutic properties of a novel platinum (II) compound AK3 and its platinum (IV) analogue AK4 in the treatment of chemically-induced breast and skin cancer models. Cytotoxicity of complexes was first evaluated using WST-1 assay in MDA-MB-231 (breast) and A375 (skin) cancer cells 72 hours posttreatment. Cellular uptake was also determined by ICP-MS. The lethal and most tolerated doses were measured for both complexes in mice. The chemotherapeutic potential was assessed in a DMBA-induced breast cancer model in rats as well as a DMBA/TPA-induced skin cancer model in mice. The biodistribution of both complexes in mice was analyzed using ICP-MS. Both compounds showed higher cytotoxic activity than cisplatin and recorded IC50 values of 0.32 and 0.6 μM for AK3 and AK4 respectively against MDA-MB-231 cells, as well as 0.36 and 0.68 μM for AK3 and AK4 respectively against A375 cells. Both AK3 and AK4 were found to be mainly actively transported into MDA-MB-231 cells at significantly higher intracellular/extracellular concentrations ratios than cisplatin. Both complexes reported low toxicities in mice, especially the platinum (IV) compound AK4. In fact, the lethal and maximum tolerated doses were relatively high, recording 25-30 and > 20 mg/kg of body weight respectively in the case of AK3, as well as > 200 and > 50 mg/kg of body weight in the case of AK4. Both complexes exhibited remarkable chemotherapeutic potential in both breast and skin cancer models by greatly reducing tumor sizes up to 13-times in the breast cancer model as well as up to 6-times in the skin cancer model, compared to control groups. No significant change in organ or body weights was observed. Also, AK3 and AK4 were both readily available in the plasma, and AK3 was still available at high levels in the liver and kidneys 24h post-injection. In conclusion, both AK3 and AK4 could be considered as promising chemotherapeutic drugs in the treatment of both breast and skin cancer as well as potential alternatives for currently adopted platinum treatment regimens reporting severe side effects.